Reliability, usefulness and construct validity of the combined basketball skill test (CBST) - Conte, D.; Smith, M. R.; Santolamazza, F.; Favero, F. G.; Tessitore, A.; Coutts, A. (Journal of Sports Sciences, 2019)
This study aimed to assess the reliability, usefulness and construct validity of the newly developed Combined Basketball Skill Test (CBST). Fifteen recreational (age = 22.8 ± 4.2 y, stature = 184.8 ± 6.5 cm, body mass = 81.6 ± 9.6 kg, training experience = 9.8 ± 5.3 y) and fifteen semiprofessional (age = 18.9 ± 3.3 y, stature = 190.5 ± 8.1 cm, body mass = 84.2 ± 11.2 kg, training experience = 11.1 ± 3.5 y) players volunteered to participate in this study. Test-retest reliability and usefulness were examined for recreational players, while construct validity was evaluated comparing the two player groups. The CBST is composed of 12 trials and its outcome measures include: completion time (sum of the 12 trial times); penalty time (sum of the times from the 12 trials); performance time (completion time + penalty time) and total number of errors. Relative reliability analysis showed acceptable ICC values (i.e. =0.70) in all the studied variables. Absolute reliability analysis showed a CV < 5% for completion (1.6%) and performance (2.0%) time, while a CV >5% is reported for the remaining variables. The usefulness of the test was considered "Marginal" and "Good" when comparing TE values with SWC02 and SWC05, respectively for all the studied variables. Likely and very likely differences were shown between recreational and semiprofessional players in all investigated variables. Results showed that the CBST is reliable, useful to detect moderate changes and valid to assess basketball skills.